THE STRUGGLE OF THE SOVIET AUTHORITY AGAINST THE «REMNANTS OF UNIAT» IN THE UKRAINIAN SSR AT THE BREAK OF THE 1970s – 1980s - PUYDA, ROMAN (Skhid, 2021)
The key methods of the Ukrainian SSR party authorities to counter the attempts of reviving the Ukrainian Greek Catholic Church in the western Ukrainian regions at the break of the 80s-90s of the XX century were considered. It was noted that in the late 1970s in this region, particularly in Galicia, Greek-Catholic believers and the clergy measurably intensified their activity, which was evident mainly in houses of worship attendance, traditional rites observance, letters issued to the Council for Religious Affairs of the Soviet Union Ministers with the requirement to register religious communities, clandestine ordination of the clergy, etc. It was stated that in order to counter the religious influence intensification of the Russian Orthodox Church on the population, as well as to prevent negative anti-social manifestations of «remnants of Uniat», local Communist Party committees and Soviet authorities carried out a number of propaganda and mass political events to expose anti-Soviet religious ideology, in particular, «the reactionary role of the Uniat Church in the history of the Ukrainian people». It was noted that the Communist Party of Ukraine took concrete measures to step up anti-religious propaganda in Western Ukrainian regions, as well as to promote the advantages of the Soviet mode of life. It was alleged that the activities of Greek Ca¬tholic believers were discussed at the Council for Religious Affairs of the Soviet Union Ministers sessions of the Ukrainian SSR in the regions of Western Ukraine, party rallies at different levels, meetings of the ideological activists of the regions, seminars of cultural and educational wor¬kers, district and regional atheist conferences. It was noted that the Communist Party of Ukraine paid considerable attention to the media, which should have covered the historical aspects of the «anti-popular backbone of Uniat Church».